The relationship between students' perception and intention to pursue accounting advanced program / Anis Barieyah Mat Bahari, Wan Mardyatul Miza Wan Tahir and Nurhazrina Mat Rahim - Mat Bahari, Anis Barieyah; Wan Tahir, Wan Mardyatul Miza; Mat Rahim, Nurhazrina (2013)
This proposed paper aims to identify the relationship between students' perception and their intention to pursue in Bachelor and Professional accounting program. Therefore. to achieve the objective. questionnaires are developed and distributed among students of Diploma in Accountancy from UiTM. Logistic regression has been used to identify the existence of the relationship. It is expected that this paper will provide an insight view whether the students' perceptions affect their intention to pursue study in accounting advanced program.